(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
In the present study, we investigate the self-association and mixed micellization of an anionic surfactant, sodium dodecyl sulfate (SDS), and a cationic surfactant, cetyltrimethylammonium bromide (CTAB). The critical micelle concentration (CMC) of SDS, CTAB, and mixed (SDS + CTAB) surfactants was measured by electrical conductivity, dye solubilization, and surface tension measurements. In this paper, the micellization of anionic surfactant sodium dodecyl sulphate (SDS) and cationic surfactant Ndodecylpyridinium chloride (DPC) in aqueous solution at various temperatures has been reported using conductivity measurements. The results show that the CMC of surfactants decreases to reach a minimum and then increases with temperature.